Cutaneous Photobiology in Basal Cell Carcinoma: A Literature Review - Alifa Aswandani; Husna, Najla Firyal; Baiq Annisa Ulfi Anggraeni; Lalu Maulana Azmi Gifari; Aisya Nur Abida; Dhiya Atsila Shofa; Muhammad Fauzan; Anang Hermansyah; Komang Puspa Dewi; Muhammad Rezky Audia Aunurrahman; Dyah Purnaning (Jurnal Biologi Tropis, 2024)
Basal cell carcinoma (BCC) is the most common type of skin cancer. BCC arises primarily from prolonged exposure to ultraviolet (UV) radiation, which has been classified as a carcinogenic agent by the International Agency for Research on Cancer (IARC). The prevalence of BCC has increased by approximately 10% annually, which serves as the basis for this article aimed at better understanding the pathophysiology linking UV exposure to BCC and to provide more comprehensive information about BCC. This study uses a literature review approach by collecting data from online databases such as PubMed, ScienceDirect, MDPI and Google Scholar. This literature review comprehensively discusses the definition, etiology, epidemiology, risk factors, pathophysiology, clinical manifestation, treatment, and prevention strategies of BCC. This study find that UV radiation causes genetic mutations, especially in tumor suppressor genes such as PTHC and p53 which lead to development of BCC. In conclusion, early detection through clinical appearance and effective prevention strategies are crucial to significantly enhancing outcomes for patients with BCC.